Potential of Long-Jawed Mackerel (Rastrelliger) Oil as the Source of Cholecalciferol and Omega-3 to Minimize the Risk of Psoriasis - Fatima Amentha Kenya; Nayla Fauziah; Pipit Fitriani (Bioinformatics and Biomedical Research Journal, 2024)
The impact of psoriasis extends beyond skin inflammation and can significantly impact the patients' mental health. Fish oil is considered an alternative to combat chronic dermatitis, mainly due to its omega-3 fatty acid and cholecalciferol contents. Long-jawed mackerel (Rastrelliger), an abundant fish in Indonesian waters, is recognized for its high omega-3 and cholecalciferol that competes with commercial and other local fish species. This study aims to analyze the nutritional content in Rastrelliger fish oil as an alternative for controlling psoriasis. This study also used the wet rendering method to compare fish oil from silver catfish and skipjack tuna. The three samples were analyzed using Fourier Transformed Infrared Spectroscopy (FTIR) spectroscopy to identify their Omega-3 and cholecalciferol contents. This process yielded 51 grams of oil from 292 grams of Rastrelliger fish. Rastrelliger's fat content was 1.83±0.03%, with a water content of 70.06±1.87%. FTIR spectrum indicated the presence of alkenes, carboxyl, methyl, and methylene groups, which are functional groups of Omega-3 fatty acids. The content in 100 grams of Rastrelliger fish was 2.2 grams of Omega-3 and 2.04 mcg of cholecalciferol. There is potential for controlling psoriasis, as the need for Omega-3 and cholecalciferol can be met. In conclusion, Rastrelliger fish oil demonstrates promising potential as a treatment measure for the autoimmune disease psoriasis.